2020
DOI: 10.1785/0220200133
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Seismic Waves Generated by Train Traffic via Modeling: Implications for Seismic Imaging and Monitoring

Abstract: Trains are now recognized as powerful sources for seismic interferometry based on noise correlation, but the optimal use of these signals still requires a better understanding of their source mechanisms. Here, we present a simple approach for modeling train-generated signals inspired by early work in the engineering community, assuming that seismic waves are emitted by sleepers regularly spaced along the railway and excited by passing train wheels. Our modeling reproduces well seismological observations of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Solving equation ( 3) instead is costly, but might be feasible, since trains are constrained to specific locations in space. Setting up the power-spectral density distribution can then benefit from progress made in train traffic modeling (Lavoué et al 2020). Ayala-Garcia et al (2021) discuss the effects of correlated sources and present a new stacking strategy to mitigate them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solving equation ( 3) instead is costly, but might be feasible, since trains are constrained to specific locations in space. Setting up the power-spectral density distribution can then benefit from progress made in train traffic modeling (Lavoué et al 2020). Ayala-Garcia et al (2021) discuss the effects of correlated sources and present a new stacking strategy to mitigate them.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments, promising observations were balanced by the difficulty of maintaining stable sources over the long-term that limits the capability of monitoring seismic velocities precisely and continuously over many years (Karageorgi et al 1992;Niu et al 2008;Tsuji et al 2018). Recent studies have shown that train traffic generates strong seismic radiation (Lavoué et al 2020). Brenguier et al (2019) and Pinzon-Rincon et al (2021) have used these train tremors to retrieve stable P waves using interferometry between arrays of sensors across the San Jacinto fault in California.…”
Section: Application To Fault Monitoringmentioning
confidence: 99%
“…( 3) instead is costly, but might be feasible, since trains are constrained to specific locations in space. Setting up the powerspectral density distribution can then benefit from progress made in train traffic modelling (Lavoué et al 2020). Ayala-Garcia et al (2021) discuss the effects of correlated sources and present a new stacking strategy to mitigate them.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments, promising observations were balanced by the difficulty of maintaining stable sources over the long-term that limits the capability of monitoring seismic velocities precisely and continuously over many years (Karageorgi et al 1992;Niu et al 2008;Tsuji et al 2018). Recent studies have shown that train traffic generates strong seismic radiation (Lavoué et al 2020). Brenguier et al (2019) and Pinzon-Rincon (2021) have used these train tremors to retrieve stable P waves using interferometry between arrays of sensors across the San Jacinto fault in California.…”
Section: P O T E N T I a L A P P L I C At I O N T O Fau Lt M O N I T O R I N Gmentioning
confidence: 99%
“…While railway infrastructure is already attracting some interest in the field of applied geophysics (Ižvolt et al, 2016;Lavoué et al, 2021), the present feasibility study specifically pushes the current limitation of mobile CRNS toward transregional monitoring. We will begin with theoretical considerations about the expected measurement uncertainty and spatial resolution, followed by a sensitivity study on the influence of vehicles and track beds using numerical simulations.…”
mentioning
confidence: 94%